Universality of Rights as an Interpretive Principle for the Indonesian Constitutional Court - Titon Slamet Kurnia; Ninon Melatyugra (Constitutional Review, 2024)
This article discusses issues regarding constitutional interpretation in general, and the interpretation of human rights provisions in the constitution in particular. The setting of the discussion is the role of the Constitutional Court of Indonesia in reviewing the constitutionality of laws based on Chapter XA of the 1945 Constitution. Constitutional interpretation is pivotal in deciding the constitutionality of laws. Therefore, this article aims to propose an interpretive principle to the Constitutional Court when interpreting human rights provisions in deciding the constitutionality of laws. The interpretive principle is the universality of rights. In other words, this article suggests the Constitutional Court adopt the universality of rights principle in interpreting Chapter XA of the 1945 Constitution. The principle of universality of rights departs from the understanding that human rights are natural rights. The interpretive principles that can be derived from the principle of universality of rights are as follows. First, recognition of unenumerated rights. Second, minimalization of the exercise of human rights limitation norms. Third, prioritization of protection of minorities. Fourth, encouraging the use of comparative approach in interpreting constitutional human rights norms. These interpretive principles are discovered through a comparative approach, in this case referring to judicial practices in other countries as well as regional and international judicial bodies that are considered relevant. The rationale behind this proposal is that human rights interpretation using the universality of rights principle can enhance the protection of human rights. Suppose judicial review of the constitutionality of laws is dedicated to enhancing human rights. In that case, constitutional interpretation should be dictated by the universality of rights principle as the interpretive principle.